Implementation of Online Learning during the Covid 19 Pandemic on Psychological Development of Grade 4 Students - Annisa Varian Febriani; Puri Pramudiani (Universitas Majalengka, 2021)
The spread of COVID-19 has changed many aspects, especially in education field. Therefore, this research was conducted to investigate the implementation of online learning on students’ psychological development. This study used a qualitative method with a descriptive approach including data collection that was carried out by taking the event that occurred and was described with the description in the form of written words, observation, and interview. The subjects in this research were 4th grade students at SDN Kayuringin Jaya 01 Bekasi. Then the researchers analyzed the data about what were the descriptions of the psychological development of grade 4 students in facing online learning. Based on the analysis conducted, the research results show: 1) The transition of the learning process from conventional learning to online learning causes many changes in students’ psychological development. 2) During online learning, there is students’ development in the cognitive, affective, and psychomotor aspects. 3) Students who experienced economic limitations find it difficult to face online learning. 4.) On the other hand, prosperous students feel happy to participate in online learning because they have a lot of time with their family.